2020
DOI: 10.1186/s12888-020-02689-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive capacities for safe clinical practice for patients hospitalised during a suicidal crisis: a qualitative study

Abstract: Background: Safe clinical practice for patients hospitalised in mental health care during a suicidal crisis is situated within a dynamic, non-linear and uncertain context. Under such complex conditions, the adaptive capacity is considered vital to handling challenges and changes in clinical care. This study aimed to explore safe clinical practice for suicidal patients hospitalised in mental health wards through understanding healthcare professionals' (HCPs') capacities to adapt to challenges and changes in cli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 57 publications
2
10
0
7
Order By: Relevance
“…As shown in the ndings, the collaborative activities often consisted of different forms of trade-offs to get appropriate information, coordinate events, negotiate prioritizations, and align different needs. Similar to other resilience in healthcare studies [52,53], this study found that the complex demands, competing interests and a diversity of stakeholders focusing on different outcomes resulted in the need to choose some type of adjustment of practice over another. While such trade-offs might be necessary to maintain situational processes and functions, adaptations and adjustments do not always provide positive outcomes for service quality and safety [2,41].…”
Section: Re Ection and Awareness -A Key To Successful Adaptationssupporting
confidence: 57%
“…As shown in the ndings, the collaborative activities often consisted of different forms of trade-offs to get appropriate information, coordinate events, negotiate prioritizations, and align different needs. Similar to other resilience in healthcare studies [52,53], this study found that the complex demands, competing interests and a diversity of stakeholders focusing on different outcomes resulted in the need to choose some type of adjustment of practice over another. While such trade-offs might be necessary to maintain situational processes and functions, adaptations and adjustments do not always provide positive outcomes for service quality and safety [2,41].…”
Section: Re Ection and Awareness -A Key To Successful Adaptationssupporting
confidence: 57%
“…39 In an interview study healthcare professionals describe they set forms and checklist aside to prioritise trust during suicide risk assessment. 40 Approximately half of the suicide victims in all cohorts had a documented prior suicide attempt, and it is shown that previous suicide attempt, especially repeated, imply higher risk for suicide persisting over decades. 41 Learning from cases of the successful treatment of patients who have survived prior suicidal crises could thus be of importance for improving suicide prevention in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…A narrative synthesis was conducted of findings across two embedded units of analysis: the experiences of patients and the experiences of HCPs (Table 1) [40]. The original data consisted of three samples collected through a multi-method case study approach [40] consisting of a systematic review of 20 peer-reviewed articles published between 1999 and 2016 on patient experiences of being hospitalised in a psychiatric ward or facility during a suicidal crisis (sample 1) [41]; individual interviews with 18 patients hospitalised during a suicidal crisis (sample 2) [42]; and focus group and individual interviews with 35 HCPs responsible for the care of suicidal patients (sample 3) [43]. The methods of the case study are described in a published study protocol [44] and the first author's PhD thesis [45].…”
Section: Methodsmentioning
confidence: 99%
“…The methods of the case study are described in a published study protocol [44] and the first author's PhD thesis [45]. Interview guides have been previously published, see supplemental file 2 in Berg et al 2020a [46] and additional file 1 in Berg et al 2020b [47].…”
Section: Methodsmentioning
confidence: 99%